A case study of waterhyacinth (Eichhornia crassipes) control in Puerto Rico using glyphosate and hand removal. (11th September 2021) - Robles, Wilfredo; Martínez, Edda L.
Abstract: Waterhyacinth [ Eichhornia crassipes (Mart.) Solm] is an aquatic invasive plant that is widespread in Puerto Rico, where it negatively effects estuaries, freshwater wetlands, potable water reservoirs, and wildlife refuges. Specifically, the tropical estuary San Juan Bay Estuary (SJBE) has been impacted with the presence of E. crassipes . Infestations have led to a reduction of water circulation in the system and have facilitated the establishment of invasive fauna. Therefore, a field study was conducted in a cove between Laguna San Jose and Peninsula Cantera to assess the use of glyphosate and hand removal as a management tool for E. crassipes control. Aquatic macroinvertebrates and water quality were also monitored as a measure of environmental impact due to management activities. Results indicated that at 2 wk after glyphosate application, E. crassipes biomass (dry weight) was significantly reduced to 0.27 kg DW m −2 at the treated plot compared with the nontreated plot, which yielded 0.62 kg DW m −2 . Fresh weight of E. crassipes decreased more than 90% when hand removal was used compared with glyphosate treatment. Dissolved oxygen and water pH were not significantly different between sites; however, water salinity increased to 8 to 9 ppt at both plots as a result of tidal activity. The order Hemiptera followed by Sarcoptiformes were common in the aquatic macroinvertebrate community. Macroinvertebrate species found associated with E. crassipes and considered natural enemies were: Orthogalumna terebrantis Wallwork, Niphograpta albigutalis (Warren), and Neochetina eichhorniae Warner. The use of glyphosate to manage E. crassipes at the Laguna San Jose was useful as a short-term control method, and its efficacy may be enhanced over time with follow-up applications in combination with hand removal.